Prevalence and Risk Factors of Substance Use Disorder in Inflammatory Bowel Disease. Issue 1 (6th February 2020) - Carney, Heather; Marrie, Ruth Ann; Bolton, James M; Patten, Scott B; Graff, Lesley A; Bernstein, Charles N; Kowalec, Kaarina
Abstract: Background: Substance use disorders (SUDs) impose a substantial individual and societal burden; however, the prevalence and associated factors in persons with inflammatory bowel disease (IBD) are largely unknown. We evaluated the prevalence and risk factors of SUD in an IBD cohort. Methods: Inflammatory bowel disease participants (n = 247) were recruited via hospital- and community-based gastroenterology clinics, a population-based IBD research registry, and primary care providers as part of a larger cohort study of psychiatric comorbidity in immune-mediated inflammatory diseases. The Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders IV was administered to participants to identify lifetime SUD, anxiety disorder, and major depressive disorder. Additional questionnaires regarding participants' sociodemographic and clinical characteristics were also completed. We examined demographic and clinical factors associated with lifetime SUD using unadjusted and adjusted logistic regression modeling. Results: Forty-one (16.6%) IBD participants met the criteria for a lifetime diagnosis of an SUD. Factors associated with elevated odds of SUD were ever smoking (adjusted odds ratio [aOR], 2.96; 95% confidence interval [CI], 1.17–7.50), male sex (aOR, 2.44; 95% CI, 1.11–5.36), lifetime anxiety disorder (aOR, 2.41; 95% CI, 1.08–5.37), and higher pain impact (aOR, 1.08; 95% CI, 1.01–1.16). Conclusions: One in six persons with IBD experienced an SUD, suggesting that clinicians should maintain high index of suspicion regarding possible SUD, and inquiries about substance use should be a part of care for IBD patients, particularly for men, smokers, and patients with anxiety disorders and pain. Abstract : Authors evaluated the prevalence and risk factors of SUD in an IBD cohort (n = 247). Forty-one (16.6%) participants experienced a lifetime SUD. Factors associated with elevated odds of SUD were ever smoking, male sex, lifetime anxiety disorder, and higher pain impact.